2011
DOI: 10.1016/j.bmcl.2010.10.112
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel hybrid from finasteride and epristeride as 5α-reductase inhibitor

Abstract: Finasteride and epristeride both inhibit 5α-reductase with high potency via competitive and non-competitive mechanism, respectively. A new hybrid of finasteride and epristeride was designed as a new 5α-reductase inhibitor based on combination principles in medicinal chemistry. Human 5β-reductase was chosen as a plausible surrogate of 5α-reductase type II and the results indicate that although the hybrid compound possesses the main bulk of epristeride, its inhibitory mechanism is same as of finasteride. The hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Among the androgens, testosterone is the most abundant in serum and secreted primarily by the testicles and ovaries. The enzyme steroid 5α-reductase catalyzes the conversion of testosterone to the most potent natural androgen, 5α-dihydrotestosterone (Yamana et al, 2010;Yao et al, 2011;Azzouni et al, 2012). Therefore, inhibition of testosterone 5α-reductase could be useful for the treatment of the above diseases.…”
Section: Effects Of the Methanol Extract From The Flowers Of M Siamementioning
confidence: 99%
“…Among the androgens, testosterone is the most abundant in serum and secreted primarily by the testicles and ovaries. The enzyme steroid 5α-reductase catalyzes the conversion of testosterone to the most potent natural androgen, 5α-dihydrotestosterone (Yamana et al, 2010;Yao et al, 2011;Azzouni et al, 2012). Therefore, inhibition of testosterone 5α-reductase could be useful for the treatment of the above diseases.…”
Section: Effects Of the Methanol Extract From The Flowers Of M Siamementioning
confidence: 99%
“…Thus, several in silico structures of steroid 5α-reductase have recently been reported to use as a surrogate structure in the screening of potential inhibitors of this enzyme. [17][18][19] Previously, it was reported that avicequinone C (5a), a furanonaphthoquinone, isolated from the methanolic extract of Avicennia marina, could inhibit the activity of steroid 5α-reductase type 1 at a micromolar scale (IC 50 =38.8 µM). This finding was based on the use of a newly developed nonradioactive human hair dermal papilla cell-based assay, which directly detects dihydrotestosterone (DHT, 2), the enzymatic product, by high performance thin layer chromatography (HPTLC).…”
mentioning
confidence: 99%
“…Functional similarities are known with 5BR (Yao et al, 2011), the structure of which is well known and present in the PDB database. Furthermore, 5AR and 5BR share the same substrate (testosterone) and inhibitor (finasteride).…”
Section: Methodsmentioning
confidence: 99%